USING THE ENVIRONMENTAL SENSITIVITY SCENARIOS OF DESERTIFICATION IN ARID AND SEMI-ARID REGIONS (A CASE STUDY OF THE AL-NASR AREA IN DHI QAR, IRAQ.) - Raad A. Abbood; A.A Jafarzadeh; A. I. Hamad; Shahin Oustan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to assess desertification and land degradation in an arid and semi-arid climate (Al-Nasr area, Dhi Qar Governorate). We used the MEDALUS and modified MEDALUS models with three scenarios, in conjunction with GIS mapping techniques, to identify desertification risks in one Iraqi governorate. After creating a desertification database containing 19 criteria, the first steps consisted of mapping four MEDALUS indicators, including soil, vegetation, climate, and land management. The next step involved adding other indicators such as irrigation water. All layers weighted by environmental conditions present in the region were then used according to the same MEDALUS framework to create a desertification map. The results showed that the modified MEDALUS models DSI2 and DSI3 performed better, with the unaffected type covering 44,623.6 and 48,817.2 hectares, representing 47% and 51% of the study area, while the severely affected type covered 41,971.7 and 35,490.8 hectares, representing 44% and 37% of the study area, respectively. For the DSI1 model, the unaffected type covered 28,968.6 hectares, representing 30.5%, while the affected type covered a very small area of ​​the study area.